Frequency of endometritis and wound infection in both elective and emergency cesarean-sections - Monroy Prado, Mauricio (2015)
OBJETIVE: To compare the frequency of endometritis and wound infection in scheduled and emergency caesareans. DESIGN: Retrospective, observational and cross-sectional epidemiological study. LOCATION: Department of Obstetrics Regional Hospital Honorio Delgado, Arequipa, Peru. MATERIALS AND METHODS: Patient at low risk for postoperative infections, cesarean during the period from January 1 to December 31, 2000. RESULTS: 11.7% of the operated patients had endometriosis emergency and surgical wound infection , compared with 6.1% in the case of scheduled cesarean, growing these differences of statistical significance. 18.3% of cesarean patients between 0 and 7 hours showed some of postoperative complications studied compared with 9.7% and 9.4% of patients operated between 8-15 and 16-23 hours respectively, and these highly significant differences. Finally, 12.8% of patients who did not receive antibiotic prophylaxis presented some complications, compared with those who did were given, who had only 5% of complications, these highly significant differences. CONCLUSIONS: endometritis and wound infection were not significantly more frequent in emergency caesarean sections. There is a highly significant difference in the time of intervention and the use of prophylactic antibiotics among patients who did cesarean endometritis and / or surgical wound infection.